Perceptions of Certified EFL Teachers Pertaining to Teacher Certification Program in Central Sulawesi, Indonesia - Anshari Syafar (Journal of Educational Sciences, 2018)
The state and condition of Indonesian teachers have gradually changed to a better nuance due to the compensation of teacher certification program (TCP). The program has conceivably raised the status of the teachers in social and economic lives. However, the impact of the program on the improvement of overall teacher‘s quality—teaching performance as mandated by Teacher and Lecturer Law remains questionable, and the big question is what and how teachers perceive and act in response to the objective of the program. The program aims not only to increase the teachers‘ salary, but also to improve the quality of their teaching performance based on the teacher standard competence, that is pedagogical, personality, social, and professional competences. Therefore, the study explore and describe certified EFL teachers‘ perceptions concerning benefits of the program on thier social and economic lives, improvement and quality of their teaching practices; perceptions on the ways management ran the program; and expectations for better services of the TCP management.